Antiproliferative effect of benzimidazole anthelmintics albendazole, ricobendazole, and flubendazole in intestinal cancer cell lines - Králová, Věra; Hanušová, Veronika; Staňková, Petra; Knoppová, Kateřina; Čáňová, Kristýna; Skálová, Lenka (Anti-cancer drugs, 2013)
This study aimed to test the antiproliferative effect of three benzimidazole anthelmintics in intestinal cancer cells and to investigate whether these drugs, which inhibit tubulin polymerization, can potentiate the efficacy of the microtubule-stabilizing drug paclitaxel (PTX). Four intestinal cancer cell lines, SW480, SW620, HCT8, and Caco2, with different origins and growth characteristics were used. The antiproliferative effect of albendazole (ABZ), ricobendazole (RBZ), flubendazole (FLU), and their combinations with PTX was tested using three different end-point viability assays, cell cycle distribution analysis, and the x-CELLigence System for real-time cell analysis. ABZ and FLU inhibited cell proliferation significantly in a concentration-dependent and time-dependent manner through cell arrest in the G2/M phase. RBZ was not effective at any concentration tested. The cell lines differed in sensitivity to FLU and ABZ, with HCT8 being the most sensitive, showing IC₅₀ values for ABZ and FLU that reached 0.3 and 0.9 μmol/l, respectively. Combinations of PTX+ABZ and PTX+FLU decreased cell viability more effectively when compared with treatment with individual drugs alone. The anthelmintic benzimidazole drugs ABZ and FLU show a significant cytostatic effect and potentiate the efficacy of PTX in intestinal cancer cells.
Keywords: Drug Resistance, Neoplasm; Intestinal Neoplasms; paclitaxel; Protein Stability; Tubulin Modulators; Cell Proliferation; albendazol; mikrotubuly; nádorové buněčné linie; G2 fáze; Anthelmintics; Cell Line, Tumor; Drug Synergism; lidé; anthelmintika; synergismus léků; Humans; Antineoplastic Agents, Phytogenic; G2 Phase; Microtubules; Inhibitory Concentration 50; Adenocarcinoma; proliferace buněk; adenokarcinom; viabilita buněk; Paclitaxel; chemorezistence; mebendazol; Albendazole; Mebendazole; inhibiční koncentrace 50; střevní nádory; protinádorové látky; Antineoplastic Agents; fytogenní protinádorové látky; stabilita proteinů; Cell Survival; modulátory tubulinu